Integrating computational thinking, game design, and design thinking: a scoping review on trends, applications, and implications for education - Chih-Hung Wu; Yu-Cheng Chien; Mei-Tzu Chou; Yueh-Min Huang (Humanities & Social Sciences Communications)
Abstract This study integrated the fields of computational thinking (CT), game design, and design thinking through a scoping review, exploring their research development trends, as well as their applications and implications for education. A scoping review of game-design-based learning in CT literature was conducted, with a focus on technology-enhanced learning and high-impact factor journals published in the ScienceDirect (SDOS) and ISI Web of Science (ISI) databases. The study analyzed various factors, including different levels of education, development tools, game development task difficulty, length of learning tasks, cognitive and emotional measurement constructs in game design, research trends, and the status of CT skills. This study combined the concept of design-thinking process, integrating CT and game-based learning topics with design thinking, to propose a human-centered, innovative educational design process for CT and game-based learning. Future studies could further explore the effects of emotional aspects and differences in cognitive levels, as well as the emotional effects of various subject concepts or prior knowledge/experience, gender, national, or cultural differences. This study offers a comprehensive understanding of the trends and dynamics in the integration of CT, game design, and design thinking to facilitate continued research and advancements in the field of game-based learning for CT education.